Analysis of HDI, Minimum Wage, and Unemployment on Poverty Levels in East Nusa Tenggara: Implications for Zakat’s Role in Economic Resilience - Nuraeni Nuraeni; Muhamad Rafi Anggara (PT. Student Rihlah Indonesia, 2026)
This study aims to analyze the effects of the Human Development Index (HDI), Provincial Minimum Wage (PMW), and unemployment rate on poverty levels across 21 districts and cities in East Nusa Tenggara (NTT) during the 2013–2023 period, as well as their implications for optimizing zakat as an instrument of economic resilience. The study employs the System Generalized Method of Moments (System-GMM) on panel data to capture the dynamic nature of poverty and address potential endogeneity among variables. The estimation results show that HDI has a negative and significant effect on poverty, indicating that improvements in human capital effectively reduce poverty. In contrast, PMW has a positive and significant effect, suggesting that wage increases have not yet translated into poverty reduction, while unemployment has a positive but insignificant effect. Simultaneously, all three variables significantly influence poverty levels. The novelty of this study lies in integrating regional macroeconomic analysis with the perspective of zakat as a complementary social policy instrument. The findings imply the importance of synergy between human development, productivity-based wage policies, and strengthening the role of zakat to enhance economic resilience and poverty alleviation in underdeveloped regions.